2018
DOI: 10.1002/jcb.27846
|View full text |Cite
|
Sign up to set email alerts
|

Flavopiridol's effects on metastasis in KRAS mutant lung adenocarcinoma cells

Abstract: Background There is still no clinically approved agent for mutant KRAS, which is the most common alteration in non–small‐cell lung cancer (NSCLC). Flavopiridol is a semisynthetic flavonoid that inhibits cell growth through cyclin‐dependent kinases in G1/S or G2/M of the cell cycle and induces apoptosis. In this study, we evaluated its effect on cellular apoptosis, survival, and metastasis mechanisms on KRAS mutant A549, Calu‐1, and H2009 cell lines. Methods The cytotoxic effects of flavopiridol on NSCLC cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The present tests revealed no activity of Bay-293 -Rapamycin combinations and Palbociclib was antagonistic in case of AsPC1. The pan-CDK inhibitor Flavopiridol was reported to exert marked toxicity in KRAS-mutated NSCLC cells [73]. Here, this compound synergized with Bay-293 for the KRAS-mutated cell lines but not for the wildtype BxPC3 cell line.…”
Section: Discussionmentioning
confidence: 86%
“…The present tests revealed no activity of Bay-293 -Rapamycin combinations and Palbociclib was antagonistic in case of AsPC1. The pan-CDK inhibitor Flavopiridol was reported to exert marked toxicity in KRAS-mutated NSCLC cells [73]. Here, this compound synergized with Bay-293 for the KRAS-mutated cell lines but not for the wildtype BxPC3 cell line.…”
Section: Discussionmentioning
confidence: 86%
“…Combined inhibition of both MEK and CDK4/6 inhibitor Palbociclib was effective in preclinical models of KRAS mutant CRC and NSCLC [ 58 , 59 ]. The pan-CDK inhibitor Flavopiridol proved highly cytotoxic in all KRAS mutant NSCLC cells at nanomolar concentrations [60] . Furthermore, silencing of CDK4 induced senescence in NSCLC with KRAS-activating mutations [61] .…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic lethal interaction with c-Myc overexpression has been observed with various targets including CDK (Yang et al, 2010;Horiuchi et al, 2012). Flavopiridol is a CDK inhibitor can have antiproliferative/proapoptotic effects in different cell lines through cell cycle arrest and by reducing c-Myc expression (Cobanoglu et al, 2016;Gokce et al, 2016;Dogan turacli et al, 2019). c-Myc overexpression has been reported in many cancer types including esophageal cancer (Tselepis et al, 2003;Dang, 2012;Jung et al, 2017;Wang et al, 2019) as we reported herein, and inhibiting CDK function using small molecule inhibitors (Senderowicz, 2003;Goel et al, 2020) sensitizing c-Myc overexpressing esophageal cancer cells to induce apoptosis can also be exploited.…”
Section: Discussionmentioning
confidence: 99%